2002
DOI: 10.1152/ajprenal.00168.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch regulates cell survival in human bladder smooth muscle cells in vitro

Abstract: . Mechanical stretch regulates cell survival in human bladder smooth muscle cells in vitro. Am J Physiol Renal Physiol 283: F1192-F1199, 2002. First published August 6, 2002 10.1152/ajprenal.00168.2002-Our understanding of the pathophysiology of the overactive bladder is poor. It has been proposed that localized contractions result in the abnormal stretching of bladder smooth muscle. We hypothesize that stretch regulates the cellular processes that determine tissue size. The purpose of this study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…Orsola et al 38 reported that cyclic stretch and relaxation of human detrusor SMC led to increased DNA and protein synthesis but apoptosis was not examined. Galvin et al 39 reported similar findings; in addition, apoptosis was decreased with stretch. On the other hand, there are reports that mechanical stretch does lead to increased apoptosis of both vascular smooth muscle 40 and renal epithelial 41 cells.…”
Section: Molecular Correlates Of Increased Apoptosis In Fetal Boomentioning
confidence: 59%
“…Orsola et al 38 reported that cyclic stretch and relaxation of human detrusor SMC led to increased DNA and protein synthesis but apoptosis was not examined. Galvin et al 39 reported similar findings; in addition, apoptosis was decreased with stretch. On the other hand, there are reports that mechanical stretch does lead to increased apoptosis of both vascular smooth muscle 40 and renal epithelial 41 cells.…”
Section: Molecular Correlates Of Increased Apoptosis In Fetal Boomentioning
confidence: 59%
“…In the mouse, TRPV2 is activated by IGF-1, a cytokine endowed with potent mitogenic and antiapoptotic [25,26] effects on cancer cells [9]; moreover, increased proliferation and survival of human bladder smooth muscle cells induced by mechanical stress is associated with increased IGF-1 levels [27]. Given the high level of IGF-1/IGF-1 receptor (IGF-1R) found in bladder tumours and its role in bladder cancer progression [28], and the strong TRPV2 increase in high-grade and -stage tumours, we would like to suggest that the TRPV2/ IGF-1/IGF-1R pathway plays an important role in the control of UC growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that both hypertrophy and hyperplasia of human airway smooth muscle cells (HASMCs) play key roles in airway remodeling (12)(13)(14)(15)(16). Many lines of evidence have demonstrated that hypertrophy in cardiomyocytes, skeletal myotubes, and smooth muscle cells is induced by various hypertrophic stimuli, including mechanical stretch (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Recently, it has been shown that miRNAs play important roles in the induction of cardiac hypertrophy as well as response to hypertrophic stimuli (28 -32).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Stretch Induces HASMCs Hypertrophy-Accumulating evidences have demonstrated that stretch can induce cardiac, skeletal, and smooth muscle cell hypertrophy (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). To test this in HASMCs, we stimulated the cells with a 1-h stretch for every 12 h up to 3 days.…”
Section: Mechanical Stretch Up-regulates Mirnas Expression-mentioning
confidence: 99%